Impairments of Motor-Cortex Responses to Unilateral and Bilateral Direct Current Stimulation in Schizophrenia - Hasan, Alkomiet; Bergener, Theresa; Nitsche, Michael A.; Strube, Wolfgang; Bunse, Tilmann; Falkai, Peter; Wobrock, Thomas (Frontiers in Psychiatry, 2013)
Transcranial direct current stimulation (tDCS) is a non-invasive stimulation technique that can be applied to modulate cortical activity through induction of cortical plasticity. Since various neuropsychiatric disorders are characterised by fluctuations in cortical activity levels (e.g. schizophrenia), tDCS is increasingly investigated as a treatment tool. Several studies have shown that the induction of cortical plasticity following classical, unilateral tDCS is reduced or impaired in the stimulated and non-stimulated primary motor cortices (M1) of schizophrenia patients. Moreover, an alternative, bilateral tDCS setup has recently been shown to modulate cortical plasticity in both hemispheres in healthy subjects, highlighting another potential treatment approach. Here we present the first study comparing the efficacy of unilateral tDCS (cathode left M1, anode right supraorbital) with simultaneous bilateral tDCS (cathode left M1, anode right M1) in schizophrenia patients. tDCS-induced cortical plasticity was monitored by investigating motor-evoked potentials induced by single-pulse transcranial magnetic stimulation applied to both hemispheres. Healthy subjects showed a reduction of left M1 excitability following unilateral tDCS on the stimulated left hemisphere and an increase in right M1 excitability following bilateral tDCS. In schizophrenia, no plasticity was induced following both stimulation paradigms. The pattern of these results indicates a complex interplay between plasticity and connectivity that is impaired in schizophrenia patients. Further studies are needed to clarify the biological underpinnings and clinical impact of these findings.